ANALYSIS OF FACTORS IN THE FORMATION OF PUBLIC-PRIVATE PARTNERSHIP AT THE REGIONAL LEVEL - KULYNYCH, Roman; SOLTIS, Maria (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The comprehensive and effective development of public-private partnership (PPP) is currently a pivotal scientific and practical objective for Ukraine. In the context of ongoing warfare and subsequent post-war recovery, PPP serves as a critically important mechanism for attracting private investments into public projects. Such investments are indispensable for the reconstruction and development of vital infrastructure, including energy, transportation, and other key sectors, which are crucial for generating gross regional product (GRP). Furthermore, the implementation of PPP models is fundamental for enhancing management efficiency, fostering job creation, and ultimately stimulating regional economic activity. This article focuses on investigating regional economic activity under martial law. The primary objective of the study is to conduct a quantitative analysis examining the relationship between Ukraine's GRP and factors influencing regional development resilience. Investigating this interaction allows for a quantitative assessment of the parameters of regional development resilience factors, facilitating the adoption of appropriate management decisions regarding the creation of necessary prerequisites for the effective development of public-private partnerships. These partnerships are considered key to promoting the country's broader recovery and sustainable economic growth. The obtained results indicate a profound transformation of Ukraine's economic model under the influence of martial law. The sustained high correlation between labor productivity and economic indicators provides grounds for cautious optimism: fundamental economic mechanisms continue to function, although their manifestations have drastically changed. At the same time, the statistical insignificance of geographical factors points to the formation of a fundamentally new economic geography, where security aspects may outweigh traditional locational advantages. This creates both challenges and opportunities for public-private partnerships, which can become a catalyst for establishing new economic clusters in secure regions. The presented model demonstrates that even under the extreme conditions of war, economic regularities retain their relevance. However, their interpretation and practical application require a radical re-evaluation, considering the new realities of public-private interaction in the current environment.
Keywords: regional development; public-private partnership; GRP; martial law; economic resilience; recovery